2014
DOI: 10.2106/jbjs.l.00536
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of MOBILITY Total Ankle Replacement

Abstract: Our findings suggest that early outcomes after total ankle replacement for patients with posttraumatic osteoarthritis are comparable with those for patients with osteoarthritis and rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…5 The current authors found the average age of patients undergoing TAA to be 62.5 years, which is slightly older than prior studies showing an average range of 50 to 60 years. 6,7,9,[17][18][19][20] Although the current study does not have survival data, an older average population age is often associated with a higher survival rate. Spirt et al 21 found that a higher survival rate (89%) in patients older than 54 years compared with patients younger than 54 years (74%).…”
Section: Discussionmentioning
confidence: 86%
“…5 The current authors found the average age of patients undergoing TAA to be 62.5 years, which is slightly older than prior studies showing an average range of 50 to 60 years. 6,7,9,[17][18][19][20] Although the current study does not have survival data, an older average population age is often associated with a higher survival rate. Spirt et al 21 found that a higher survival rate (89%) in patients older than 54 years compared with patients younger than 54 years (74%).…”
Section: Discussionmentioning
confidence: 86%
“…MobilityÔ prostheses had been implanted and, with 33% of the total ankle replacements recorded in the registries, represents the most frequently implanted prosthesis worldwide. However, just as with all total ankle replacements studied, the short-term incidence of revision increases with longer term follow-up, and the most common failure mechanisms of aseptic osteolysis and component subsidence predominantly involving the talar component become more evident (41)(42)(43)45,46,48,49,51). Accordingly, the value of including total ankle replacement in national joint registries is obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analysis of our TAR data has not demonstrated any evidence of a “learning curve” in terms of outcomes. 12…”
Section: Discussionmentioning
confidence: 99%